2011
DOI: 10.1590/s0037-86822011005000021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of human herpesvirus 6B primary infection by polymerase chain reaction in young children with exanthematic disease

Abstract: INTRODUCTION: Exanthem subitum is a classical rash disease of early childhood caused by human herpesvirus 6B (HHV-6B). However, the rash is frequently misdiagnosed as that of either measles or rubella. METHODS: In this study, a nested multiplex polymerase chain reaction (PCR) was used to diagnose HHV-6B primary infection, differentiate it from infections caused by HHV-6A and compare it to antibody avidity tests. The samples were separated into case group and control group according to the results of the indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Human Herpesvirus 6 and 7 (HHV‐6 and HHV‐7) are classified in Betaherpesvirena and Roseola virus genus 1,2 . For the first time, HHV‐6 was isolated from AIDS patients and was cultured in T cell culture in 1986 3,4 . Four years later, HHV‐7 was isolated from a healthy blood donor's peripheral blood lymphocytes 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Human Herpesvirus 6 and 7 (HHV‐6 and HHV‐7) are classified in Betaherpesvirena and Roseola virus genus 1,2 . For the first time, HHV‐6 was isolated from AIDS patients and was cultured in T cell culture in 1986 3,4 . Four years later, HHV‐7 was isolated from a healthy blood donor's peripheral blood lymphocytes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Primary infections with clinical symptoms in approximately 30% of children are known as roseola or exanthema subitum 9 . Exanthema is a classic early childhood disease with sudden onset of high fever, which lasts 3 to 4 days, and rashes appear as the baby's temperature decreases 3,5 . HHV‐7 is also the cause of about 5%–10% of roseola cases 3,6,10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, the first population-based study reporting the prevalence of HHV-6 antibodies was performed by Linhares et al (1991) , who found rates of 76.5% for Brazilians and 77.2% for Japanese immigrants. Since then, studies on HHV-6 seroprevalence and DNA detection (SybrGreen ® based technology) have been reported in solid organ transplant recipients ( de Freitas et al 1994 , de Freitas & Linhares 1997, Oliveira et al 2001 , Canto et al 2008 , Cavalcanti 2011 , Magalhães et al 2011 , Guardia et al 2012 , 20, 2014 ), but the detection by real-time quantitative polymerase chain reaction (qPCR) (TaqMan ® technology based) in HSCT recipients has not been systematically performed in Brazilian patients. The development of diagnostics and immunology methods for HHV-6 detection can provide better surveillance of HHV-6 reactivation ( de Pagter et al 2008b , 2010, Betts et al 2011 , Gerdemann et al 2013 , Leibovitch et al 2014) .…”
mentioning
confidence: 99%